The "Boast of Antiquity": Pulpit Politics Across the Atlantic Archipelago during the Revolution of 1688. Issue 3 (31st July 2014) - Key, Newton
<x content-type="archive" xml:space="preserve">Abstract</x> John Locke and many others noted the vibrant political commentary emanating from the pulpit during the Glorious Revolution. Preachers from the full confessional spectrum in England, and especially in Scotland, Ireland, and the colonies, used occasional or state sermons to explain contemporary upheavals from the perspective of God's law, Natural law, and Civil law. Most surprising is the latter, clerical reference to civil history and ancient origins, which preachers used to answer contemporary questions of conquest and allegiance. Clergy revisited the origins and constitutional roots of the Britons, Anglo-Saxons, Scots, and Irish, and deployed histories of legendary kings and imaginary conquests to explain and justify the revolutionary events of 1688–1692. Sermons of this revolutionary era focused as much on civil as on sacred history, and sought their true origins in antiquity and the mists of myth. Episcopalian preachers, whether Church of Ireland, Scottish Episcopalian, or Church of England, seem to have been especially inspired by thanksgiving or fast days memorialized in the liturgical calendar to ponder the meaning of a deep historical narrative. Scots, Irish, and Massachusetts clergy claimed their respective immemorialism, as much as the English did theirs. But, as they re-stated competing Britannic constitutions and origin myths explicitly, they exposed imperial rifts and contradictions within the seemingly united claim of antiquity. By the beginning of the next reign and century, state sermons depended more upon reason and less upon a historicized mythic antiquity.